2016
DOI: 10.1242/jeb.138784
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones correlate with field metabolic rate in ponies,Equus ferus caballus

Abstract: During winter, free-living herbivores are often exposed to reduced energy supply at the same time that energy needs for thermoregulation increase. Several wild herbivores as well as robust horse breeds reduce their metabolism during times of low ambient temperature and food shortage. Thyroid hormones (THs) affect metabolic intensity and a positive effect of THs on basal metabolic rate (BMR) has been demonstrated in mammals and birds. As BMR and field metabolic rate (FMR) are often assumed to be intrinsically l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 61 publications
(84 reference statements)
1
13
0
Order By: Relevance
“…We believe that determinations of total T4 levels are as important as those of fT4 levels in assessing thyroid gland function. This is supported by previous reports showing that fT4 concentrations in plasma are highly correlated with total T4 concentrations [ 3 , 8 , 38 ]. Interestingly, total T4 levels in yearlings obtained in our RIA, 225.98 ± 20.89 n g/m l , were dramatically different from the reference values of 35 n g/m l [ 27 ] and 68.68 ± 2.0 n g/m l in horses at 6 months to 1 year of age, or 34.61 ± 0.92 n g/m l in horses 1–3 years of age [ 17 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We believe that determinations of total T4 levels are as important as those of fT4 levels in assessing thyroid gland function. This is supported by previous reports showing that fT4 concentrations in plasma are highly correlated with total T4 concentrations [ 3 , 8 , 38 ]. Interestingly, total T4 levels in yearlings obtained in our RIA, 225.98 ± 20.89 n g/m l , were dramatically different from the reference values of 35 n g/m l [ 27 ] and 68.68 ± 2.0 n g/m l in horses at 6 months to 1 year of age, or 34.61 ± 0.92 n g/m l in horses 1–3 years of age [ 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…Radioimmunoassay (RIA) is considered the gold standard method to determine thyroid hormone levels, because RIA exhibits high sensitivity and specificity and low detection limits [ 2 , 14 , 15 , 20 , 21 , 29 , 30 ]. Furthermore, equilibrium dialysis [ 2 ], ultrafiltration [ 31 ], enzyme immunoassay [ 3 , 23 , 33 , 34 ], chemiluminescence immunoassay [ 10 , 28 ], chemiluminescent enzyme immunoassay [ 11 ] and electrochemiluminescence immunoassay [ 10 , 39 ] are available to evaluate thyroid function in many species. Nonetheless, reference values of thyroid hormone concentrations vary substantially by measurement techniques used and laboratories performing the assays.…”
mentioning
confidence: 99%
“…Accordingly, a positive relationship between thyroid hormone levels and metabolic rate has been found in captive reptiles (Joos and John-Alder, 1990), birds (Vézina et al, 2009) and mammals (Banta and Holcombe, 2002;Brinkmann et al, 2016;Li et al, 2010), including humans (reviewed in Hulbert, 2000;Kim, 2008). In contrast, other studies report no relationship between metabolic rate and thyroid hormones in captive mammals (Nilssen et al, 1984;Ostrowski et al, 2006), including humans (Bernstein et al, 1983;Johnstone et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormones are believed to play a key role in the regulation of seasonal and acute changes in metabolism, and the regulating function of thyroid hormones should be especially important during periods of reduced food availability, when animals should lower energy expenditure (Brinkmann et al, 2016;Flier et al, 2000;Fuglei and Øritsland, 1999;Zhan et al, 2009). Accordingly, laboratory studies on humans (Carlson et al, 1977;Gardner et al, 1979), other mammals and birds found that thyroid hormone levels decrease when individuals are food deprived (Brinkmann et al, 2016;Diano et al, 1998;Mustonen et al, 2008;Nieminen et al, 2001) and increase during periods of high food intake (Fuglei et al, 2000;Stokkan et al, 1985). However, few field studies tested whether free-living animals show seasonal changes in thyroid hormone levels as an adaptation to changes in food availability.…”
Section: Introductionmentioning
confidence: 99%
“…For chronically cold weather, serum thyroid hormone and metabolic rate did not change significantly from autumn to spring [ 28 ]. In the case of long-term exposure to low temperatures in other species, thyroid hormone levels increased and resulted in stimulation of metabolism and heat production in sows [ 1 ], sheep [ 34 ], and cattle [ 11 ]; horses, on the other hand, employed a state of hypometabolism to keep their bodies warm [ 5 , 6 , 26 ].…”
Section: Discussionmentioning
confidence: 99%